2004
DOI: 10.1603/0022-0493-97.6.2067
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Physiological Resistance of the German Cockroach to Gel Baits (Blattodea: Blattellidae)

Abstract: A gel bait-resistant German cockroach, Blattella germanica (L.), strain Cincy was collected in Cincinnati, OH. This strain exhibited a high level of behavioral resistance to Avert (0.05% abamectin) and Maxforce FC (0.01% fipronil) gel baits. Topical application assays indicated moderate levels of physiological resistance of the Cincy strain to abamectin and fipronil. Resistance ratios (based on LD50 values from topical applications) to abamectin and fipronil were 2.5 and 8.7, respectively. The Cincy strain of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 14 publications
2
26
0
5
Order By: Relevance
“…Although chlorpyrifos is considered a nonselective product , this acaricide did not affect the evaluated behavioural parameters of N. baraki, thereby suggesting that there may not be a relationship between the behavioural effects and toxicity for chlorpyrifos. Several authors have reported this same result for deltamethrin, permethrin, abamectin and fipronil (Kongmee et al 2004;Wang et al 2004;Jallow and Hoy 2005). The fact that carbosulfan changed the behavioural parameters confirmed the low tolerance of the mite to this product, as it was necessary to use the LC 50 values in the bioassays because the LC 99 concentrations paralysed the predator before the end of the experiment.…”
Section: Discussionmentioning
confidence: 62%
“…Although chlorpyrifos is considered a nonselective product , this acaricide did not affect the evaluated behavioural parameters of N. baraki, thereby suggesting that there may not be a relationship between the behavioural effects and toxicity for chlorpyrifos. Several authors have reported this same result for deltamethrin, permethrin, abamectin and fipronil (Kongmee et al 2004;Wang et al 2004;Jallow and Hoy 2005). The fact that carbosulfan changed the behavioural parameters confirmed the low tolerance of the mite to this product, as it was necessary to use the LC 50 values in the bioassays because the LC 99 concentrations paralysed the predator before the end of the experiment.…”
Section: Discussionmentioning
confidence: 62%
“…Glucose aversion might furthermore be linked with physiological costs or adaptations, which might in turn have competitive consequences in the absence of baits if wild‐type (WT) individuals reinvade. Mild aversion to a range of mono‐ and disaccharides has been indicated in a few wild German cockroach populations with long‐term exposures to sugar‐containing baits (Wang et al ., , ), and Shik et al . () found that GA nymphs given choice ingested less carbohydrate than WT nymphs while they selected a similar protein intake.…”
Section: Introductionmentioning
confidence: 94%
“…Provisioning of toxic baits in the environment of German cockroaches is often the most efficacious measure of cockroach control (Appel, ; Schal & Hamilton, ). However, like other pest control measures, baits have selected for the evolution of physiological resistance to toxins used in baits (Schal, ; Wang et al ., ; Gondhalekar & Scharf, ), as well as behavioural resistance induced by bait components (Silverman & Bieman, ; Strong et al ., ; Silverman & Ross, ; Ross, ; Wang et al ., ). A remarkable feature of formulated synthetic baits is that the toxin is normally coupled with phagostimulatory compounds to promote its ingestion, and sugars, in particular glucose, are used as phagostimulants in multiple bait formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding resistance in weeds and low-dosage herbicide applications, Renton et al (2011) conducted modeling and demonstrated no effect of dosage on the risk of monogenic resistance but an increased risk of herbicide resistance in certain cases of polygenic resistance, when weeds are exposed to low-dosage herbicide regimes. All genetic population modeling studies focus exclusively in genetic/physiological resistance; however, animals such as insects are also known to potentially develop behavioral resistance or avoidance (Martini et al 2012;Wang et al 2004;Hostetler and Brenner 1994).…”
Section: Snapcard Predictions and Spray Coverages Published Elsewherementioning
confidence: 99%
“…A low spray coverage means that target arthropod pests in a crop canopy are presented with choices between treated and untreated portions of crop leaves. A possible consequence of low and inconsistent pesticide spray coverages is that target pests develop behavioral avoidance or resistance (Georghiou 1972), and it has been documented in several arthropod species, including German cockroaches [Blatella germanica L. (Dictyoptera: Blattellidae)] (Hostetler and Brenner 1994;Wang et al 2004), diamondback moths (Plutella xylostella L, Lepidoptera: Plutellidae) (Sarfraz et al 2007;Hoy 2007, 2006), and spider mites [ Te t r a n y c h u s c i n n a b a r i n u s B o i s d u v a l ( A c a r i : Tetranychidae)] (Martini et al 2012). Likely consequences of low spray coverage and target pests developing behavioral avoidance/resistance include reduced pest suppression and therefore an increase in number of applications (because after a spray failure, farmers have to come back and spray again), increased risk of environmental contaminations, and potential loss of agricultural productivity.…”
Section: Introductionmentioning
confidence: 99%